2021
DOI: 10.1002/hec.4433
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational health mobility: Evidence from Danish registers

Abstract: This paper is one of the first to investigate mobility in overall health using high‐quality administrative data. The attractiveness of this approach lies in objective health measures and large sample sizes allowing twin analyses. I operationalize health mobility by a variety of statistics: rank–rank slopes, intergenerational correlations (IGCs) and sibling and identical twin correlations. I find rank–rank slopes and IGCs in the range 0.11–0.15 and sibling correlations in the range 0.14–0.20. Mobility in health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…In contrast, the intergenerational correlation for income is typically much smaller. For gross income including public transfers Landersø and Heckman (2017) estimate it to be 0.21, while Andersen (2021), studying total income before deductions and taxes, finds values between 0.05-0.06 (maternal income) and 0.13-0.21 (paternal income). Our measure of disposable family income reflects the progressivity of the Danish tax system, so these estimates are probably too large.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the intergenerational correlation for income is typically much smaller. For gross income including public transfers Landersø and Heckman (2017) estimate it to be 0.21, while Andersen (2021), studying total income before deductions and taxes, finds values between 0.05-0.06 (maternal income) and 0.13-0.21 (paternal income). Our measure of disposable family income reflects the progressivity of the Danish tax system, so these estimates are probably too large.…”
Section: Discussionmentioning
confidence: 99%
“…Intergenerational correlations for health tend to be even smaller, at least with respect to fathers. Andersen (2021) finds values between 0.11-0.12 (paternal health) and 0.13-0.14 (maternal health). x Andersen (2021) finds rank-rank slopes for intergenerational health outcomes in Denmark that are only half the size of those found by Halliday et al (2018) for the U.S., a country with a considerable fraction of uninsured people.…”
Section: Discussionmentioning
confidence: 99%
“…This means that between 18–21 percent of mental health of the parents is transmitted to their children—a finding common in the literature in this field. 1824 The study has additionally shown that early life disadvantage is an important factor influencing the intergenerational correlation in mental health, providing evidence on the importance of contextual factors in reducing intergenerational health disadvantage and inequalities.…”
Section: Introductionmentioning
confidence: 90%
“…For example, international comparisons suggest that countries with more extensive welfare state provision and universal health care systems, such as those in Nordic countries, tend to have higher levels of health mobility (i.e., less intergenerational persistence) compared to countries like the United States that have less extensive public service provision. 21 Nevertheless, thus far, there have been very few studies focusing on exploring intergenerational correlations in mental health and the potential drivers of this relationship. Two notable exceptions include the studies by Brown 22 and Vera-Toscano and Brown.…”
Section: Introductionmentioning
confidence: 99%
“…Solon, 1999 andDevereux, 2011, for overviews) and, in particular, the quite small literature on intergenerational persistence in health outcomes (see e.g. Andersen, 2019, Björkegren et al, 2019Halliday et al, 2018;Petersen, Kragh Andersen and Sørensen, 2005;and Sørensen et al, 1988). In the literature on intergenerational mobility there is an increasing number of studies using adoptees to distinguish between pre-and post-birth factors.…”
Section: Introductionmentioning
confidence: 99%